A survey on communication components for IoT-based technologies in smart homes - Zaidan, Aws Alaa; Zaidan, Bilal Bahaa; Yas, Qahtan Majeed; Albahri, O.S.; Albahri, A.S.; Alaa, Mussab; Jumaah, Fawaz Mohammed; Talal, Mohammed; Tan, Kian Lam; Shir, W.L.; Lim, Chen Kim (Kluwer (now part of Springer), 2018)
The new and disruptive Internet of Things (IoT)-based technologies being used in smart homes have significantly bounded and dispersed communication components. To examine these technologies and provide researchers with a clear vision toward this area, we must be aware of the utilized approaches and the existing limitations in this line of research. To this end, an extensive search was conducted for articles dealing with (a) smart homes, (b) IoT, and (c) related applications were comprehensively reviewed and a coherent taxonomy for these articles was established. ScienceDirect, IEEE Xplore, and Web of Science databases were checked for articles on IoT-based smart home technologies. The retrieved articles were then filtered based on specified criteria “Communication components aspects”, and 82 articles were eventually selected and classified into four categories. The first category included articles that representing internet devices in a framework or model that follows the requirements of the stage in which any system is developed, the second category included analytical studies that monitor the possible changes in the variables used in a specific case study, the third category included evaluation, comparative studies, and assessing their worth or merit, and the fourth category included reviews and surveys a review and survey of the communication components of IoT-based smart home technologies. The motivation for using IoT-based technologies in smart homes, the issues related to application obstruction, and the development and utilization of smart homes are then examined based on the findings from the literature. With the exception of the 82 articles reviewed earlier, the telecommunication standards and concepts of this research were covering IoT solutions, communication protocols, IoT stack protocol, and quality of service for IoT based smart home technologies.